2010
DOI: 10.1007/s12070-011-0118-9
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Adenoidectomy with Microdebrider

Abstract: To describe endoscopic power assisted adenoidectomy and review the experience with the procedure demonstrating its safety and efficacy. Prospective study of 44 patients aged between 7 to 15 years undergoing power assisted adenoidectomy between Jan 2004 and July 2006. Tertiary care private teaching hospital. Forty four consecutive children with adenoid hypertrophy undergoing power assisted adenoidectomy. Therapeutic endoscopic adenoidectomy using microdebrider. Operative time, blood loss, complications, complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 15 publications
1
25
1
1
Order By: Relevance
“…In group A, the mean recovery period was 3.5 and 2.93 days in group B (p \ 0.05) [7]. Similarly, a study by Somani et al [12], showed less morbidity after endoscopic power assisted adenoidectomy. After the above discussions with reference to national and international studies, it is our impression that the adenoid tissue removed during endoscopic assisted microdebrider adenoidectomy is more acceptable as its use allows a more complete removal of the adenoid tissue and in a more precise manner compared with conventional methods.…”
Section: Number Of Cases Completeness Of Removal On Nasal Endoscopymentioning
confidence: 88%
See 4 more Smart Citations
“…In group A, the mean recovery period was 3.5 and 2.93 days in group B (p \ 0.05) [7]. Similarly, a study by Somani et al [12], showed less morbidity after endoscopic power assisted adenoidectomy. After the above discussions with reference to national and international studies, it is our impression that the adenoid tissue removed during endoscopic assisted microdebrider adenoidectomy is more acceptable as its use allows a more complete removal of the adenoid tissue and in a more precise manner compared with conventional methods.…”
Section: Number Of Cases Completeness Of Removal On Nasal Endoscopymentioning
confidence: 88%
“…With reference to national and international studies, the mean age of presentation in both the groups of our study coincides well with other studies. Adenoid hypertrophy can present with varied symptoms ranging from nasal obstruction, nasal discharge, post nasal discharge, snoring, ear ache, decrease hearing, sleep apnoea to delayed defective speech [11,12]. Hypertrophied adenoid tissue causing habitual mouth breathing may result in dentoskeletal malocclusions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations